The effect of indigenous leadership on perceptions of educational relevance among primary school teachers in the Hadiya zone, Central Ethiopian Region - Ababora, Nega; Molla Demissie, Mesfin; Dobbo, Temesgen (Journal of Interdisciplinary Studies in Education, 2026)
This study aimed to examine the influence of indigenous leadership on teachers' perceptions of educational relevance in primary schools in the Hadiya Zone of the Central Ethiopian Region. A quantitative method was employed in an explanatory research design, and 383 primary school teachers were selected using simple and proportionate random sampling. The study hypothesized the effect of indigenous leadership dimensions (working with the indigenous community, advocacy and visibility, vision and influence, resilience and persistence, and institutional authority) on educational relevance using a multiple linear regression model. The overall regression model significantly explained 70.5% of the variance in educational relevance (R² = 0.705, F(5, 377) = 179.998, p < .001), with indigenous leadership exerting a statistically significant positive influence. All the dimensions had a positive effect, and advocacy and visibility had the largest effect (β=0.348, p < 0.001). The findings imply that institutions of higher learning that train teachers and leaders should consider adopting indigenous leadership principles in their teaching and training. Thus, the study suggests that policymakers and school administrators in the Hadiya Zone and other settings promote and institutionalise local leadership practices, especially those that promote advocacy and visibility, to enhance the perceived value of primary education among teachers.